Park Street Church and Tremont Street during a snowstorm, January 9, 1923 - McCormick, Charles (Tufts Archival Research Center, 2005)
Street-level view north-northeast of Tremont Street and the Park Street Church, located at 119 Tremont Street, during a snowstorm. The facade of the church faces east-southeast. The subway entrance at Boston Common is visible near the lower-right side of the photograph. Workers shovel snow on the pathway through Boston Common, and pedestrians are included in the photograph. Park Street Church designed by Peter Banner, 1810 9 15/16 x 7 15/16 Photographs